2007
DOI: 10.1111/j.1439-0507.2007.01437.x
|View full text |Cite
|
Sign up to set email alerts
|

The genetic epidemiology of tinea versicolor in China

Abstract: SummaryTo study the clinical and epidemiological profile of Pityriasis versicolor (PV) and to determine the possible genetic model for PV in Chinese Han, we investigated 503 patients with PV who were recruited by a questionnaire method. Statistical analysis, heritability and complex segregation analysis were performed using EPI INFO 6.0, SPSS 10.0, the Falconer method and the SAGE-REGTL programs. In the total 503 PV patients, the mean age of onset was 22.85 ± 10.36 years. For male and female patients, the peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 26 publications
(80 reference statements)
1
27
0
Order By: Relevance
“…Several works in the literature studied pityriasis versicolor in relation to gender. Many studies show higher prevalence in male subjects, [10][11][12][13] while in other studies female patients were more affected. Apparently, there is no predominance between genders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several works in the literature studied pityriasis versicolor in relation to gender. Many studies show higher prevalence in male subjects, [10][11][12][13] while in other studies female patients were more affected. Apparently, there is no predominance between genders.…”
Section: Discussionmentioning
confidence: 99%
“…These authors believe that there is a polygenetic and multifactorial inheritance and that in these cases the disease occurs earlier, has long duration, and recurrences are more frequent. 13 Other predisposing factors were use of oil or moisturizers in the skin and the use of occlusive clothing. These habits may predispose the individual to the development of lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Luk et al [28] also reported a significant relationship between family history of atopy and eczema, indicating a correlation between positive family history and eczema [33]. Similarly, He et al [22] observed that in respondents with a positive family history of Tinea versicolor, infection was recurrent and it lasted longer than in those with a negative family history.…”
Section: Family Historymentioning
confidence: 96%
“…These results are consistent with several studies. For instance, Mahmoudabadi et al [20], Rasi et al [21] and He et al [22] found that more males were affected with versicolor infection than women in Iran and China respectively. However, among children, the most common dermatophyte infection is Tinea capitis [6].…”
Section: Gender and Skin Infectionmentioning
confidence: 99%
See 1 more Smart Citation